2016
DOI: 10.5330/1096-2409-20.1.159
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Factors that Relate to School Counselors' Knowledge and Skills in Multi-Tiered Systems of Support

Abstract: Using structural equation modeling (SEM), the authors examined factors that relate to school counselors' knowledge and skills in multi-tiered systems of support (MTSS). A sample of 4, 066 school counselors participated in an online survey. Results indicated that school counselors' time spent on ASCA-aligned activities predicted more MTSS knowledge and skills. This article presents implications for school counselor training programs, counselor educators, school counselor leaders, and practicing school counselor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 50 publications
1
25
0
Order By: Relevance
“…Similarly, previous research has found that school counselors report not having enough time to provide mental health services because of other demands (Carlson & Kees, 2013). These results may also be related to Olsen, Parikh-Foxx, Flowers, and Algozzine's (2016) findings that school counselors needed more training to implement multitiered systems of support (MTSS). Olsen et al (2016) argued that training in MTSS would increase the capacity of school counselors to reach more students and provide services.…”
Section: Self-efficacy For Enhancing Students' Career and College Reamentioning
confidence: 73%
See 1 more Smart Citation
“…Similarly, previous research has found that school counselors report not having enough time to provide mental health services because of other demands (Carlson & Kees, 2013). These results may also be related to Olsen, Parikh-Foxx, Flowers, and Algozzine's (2016) findings that school counselors needed more training to implement multitiered systems of support (MTSS). Olsen et al (2016) argued that training in MTSS would increase the capacity of school counselors to reach more students and provide services.…”
Section: Self-efficacy For Enhancing Students' Career and College Reamentioning
confidence: 73%
“…These results may also be related to Olsen, Parikh-Foxx, Flowers, and Algozzine's (2016) findings that school counselors needed more training to implement multitiered systems of support (MTSS). Olsen et al (2016) argued that training in MTSS would increase the capacity of school counselors to reach more students and provide services. As such, training in career and college readiness may affect school counselors' ability to provide postsecondary readiness services for all students.…”
Section: Self-efficacy For Enhancing Students' Career and College Reamentioning
confidence: 76%
“…The ASCA National Model (2012) recommends that school counselors spend 80% or more of their time in direct or indirect student services. When secondary school counselors spent more time engaging in ASCA-aligned duties, they were more skilled in implementing support systems that directly impacted student’s academic, social/emotional, and career development (Olsen, Parikh-Foxx, Flowers, & Algozzine, 2016).…”
Section: School Counselor Job Dutiesmentioning
confidence: 99%
“…When administrators, teachers, and students expect school counselors to engage in duties misaligned with their expertise, counselors are unable to complete the duties they were trained to perform (DeMato & Curcio, 2004; Gruman et al, 2013; Scarborough & Culbreth, 2008). Spending time on these noncounseling activities prevents school counselors from engaging in counseling duties, which have been shown to have the greatest impact on students’ academic, social/emotional, and career outcomes (Carey & Dimmitt, 2012; Lapan, Gysbers, & Kayson, 2006; Olsen et al, 2016; Wilkerson et al, 2013; Whiston, Tai, Rahardja, & Eder, 2011).…”
Section: School Counselor Job Dutiesmentioning
confidence: 99%
See 1 more Smart Citation